A construção da autonomia de bebês e crianças bem pequenas segundo a abordagem de Emmi Pikler - Silva, Ana Vitória Batista da (Brasil, 2023)
This research aims to discuss some aspects of the Hungarian pediatrician Emmi Pikler's approach to building the autonomy of babies and very young children. The pediatrician believed that the child should explore the world by himself, in this way he would be able to develop his autonomy and self-confidence. Among the various aspects of the aforementioned reference, Pikler directs us to the concept of free movement, the value of autonomous activities and free play. For this, a bibliographical research was carried out based on studies on autonomy, by authors such as: CHOKLER (2014), FALK (2011), KALLÓ; BALOG (2017), TARDOS (1992) and FOCHI; KNIGHT; DRECHLE (2016). A documental analysis of the National Curriculum Guidelines for Early Childhood Education (BRASIL, 2010), the Law of Guidelines and Bases of National Education (BRASIL, 1996), Federal Constitution (BRASIL, 1988) and observations of the daily life of a kindergarten class was also carried out. in a school located in the city of Manaus, which works with Emmi Pikler's approach. In this sense, in its results, the research allowed us to reflect on the ways in which institutions and parents are working to build autonomy with those who have just arrived in the world, recognizing the value of freedom of movement and autonomous activities and the richness of games of babies and very young children as conditions for their integral development.